(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Mercury is an environmental neurotoxicant that triggers structural and physiological alterations in different brain parts. The hippocampus is associated with learning and memory, and injury to this brain part may lead to behavioural and cognitive changes. Phoenix dactylifera (date palm) has been demonstrated to possess a variety of medical benefits. This study comparatively assessed the neuroprotective property of aqueous and ethanol fruit pulp extracts of P. dactylifera in a rat model of mercury-triggered hippocampal changes using microscopic examinations. Twenty-eight Wistar rats were divided into seven groups (I–VII, n=4). Group I (control) was administered distilled water (2ml/kg); group II was administered mercuric chloride, HgCl2 (5mg/kg); group III was administered vitamin C (100mg/kg) as reference drug +HgCl2; groups IV and V were administered aqueous extract (250mg/kg and 500mg/kg, respectively) +HgCl2, while groups VI and VII were administered ethanol extract (250mg/kg and 500mg/kg, respectively) +HgCl2. Extracts’ neuroprotective property were evaluated using histological and histometric assessments of CA1 and CA3 hippocampal sub-regions. Results revealed cytoarchitectural changes including karyopyknosis, basophilic necrosis and remarkably decreased histometric features of hippocampal pyramidal neurons in HgCl2-treated group relative to control. Administration of the extracts remarkably ameliorated mercury-induced degenerative changes by preservation of cytoarchitectural features comparable to reference drug. Comparatively, neuroprotective efficacies of the extracts are relatively similar, especially at doses of 500mg/kg and could be attributed to antioxidant activities of constituent phytochemicals. Results suggest that aqueous and ethanol fruit pulp extracts of P. dactylifera may prove efficacious in ameliorating mercury-triggered microscopic alterations in the hippocampus of Wistar rats.